2000
DOI: 10.1038/sj.ijo.0801203
|View full text |Cite
|
Sign up to set email alerts
|

The association between television viewing and overweight among Australian adults participating in varying levels of leisure-time physical activity

Abstract: OBJECTIVES: To investigate the effect of physical activity on the association between television viewing and overweight (body mass index (BMI) ! 25 kgam 2 ). DESIGN: Cross-sectional study administered by interview to adults randomly selected from the electronic white pages. SUBJECTS: 3392 adults (64% response rate) from a representative population sample in the State of New South Wales, Australia. MEASUREMENTS: Self-reported height and weight, two-week leisure-time physical activity recall, one-week average te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
162
6
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(197 citation statements)
references
References 28 publications
21
162
6
5
Order By: Relevance
“…In this representative Scottish sample, both physical activity and sedentary behaviour were independently related to BMI and WC. This independence in relation to obesity has been previously reported in European Union (6) and Australian (7) studies which, unlike the present study, did not differentiate between physical activity types and did not adjust for occupational physical activity. Our findings are in agreement with the Australian study where high levels of physical activity were not always protective against excess adiposity, if it was counteracted by high sedentary behaviour (7) .…”
Section: Physical Activity Sedentary Time and Obesitysupporting
confidence: 83%
See 1 more Smart Citation
“…In this representative Scottish sample, both physical activity and sedentary behaviour were independently related to BMI and WC. This independence in relation to obesity has been previously reported in European Union (6) and Australian (7) studies which, unlike the present study, did not differentiate between physical activity types and did not adjust for occupational physical activity. Our findings are in agreement with the Australian study where high levels of physical activity were not always protective against excess adiposity, if it was counteracted by high sedentary behaviour (7) .…”
Section: Physical Activity Sedentary Time and Obesitysupporting
confidence: 83%
“…This independence in relation to obesity has been previously reported in European Union (6) and Australian (7) studies which, unlike the present study, did not differentiate between physical activity types and did not adjust for occupational physical activity. Our findings are in agreement with the Australian study where high levels of physical activity were not always protective against excess adiposity, if it was counteracted by high sedentary behaviour (7) . In the present study, prevalence of obesity was still high in respondents who met the obesity-preventing recommendation and reported $ 4 h of TVSE per d (one in five by BMI-OB; one in four by WC-OB).…”
Section: Physical Activity Sedentary Time and Obesitysupporting
confidence: 83%
“…With time trends suggesting that sedentary behaviours are increasing, a growing number of studies are now focusing on, or including measurements of sedentary behaviour. Several cross-sectional studies in adults 3,34 and children 2,35,36 demonstrate a relationship between longer hours of television viewing and increased fatness, and it is likely that since a large proportion of the population watch television on a daily basis, duration of viewing will show stronger relationships than frequency, which might explain our null relationship at 16 y. However, longitudinal studies report less consistent results.…”
Section: Bmi and Television Viewingmentioning
confidence: 75%
“…2 Studies linking the convergence of these two trends have demonstrated that high levels of TV use are significantly associated with child overweight. [3][4][5][6] The average American household with children aged 8-18 years has three TV sets, and 68% of children have a TV in their own bedroom. 2 Averaging at least 3 h a day, child media exposure to TV exceeds other media, including exposure to videos/DVDs/movies, print media, audio media, computers and video games.…”
Section: Introductionmentioning
confidence: 99%
“…2 High amounts of TV use have been associated with many negative outcomes, including poor scholastic performance, 7,8 sleep deprivation, 9,10 child requests for advertised foods, 11 eating fewer fruits and vegetables and more pizza/snack food/soda, 12 greater consumption of high-fat foods 13 and higher BMI. [4][5][6]14 Overweight is associated with many diseases, 1,[15][16][17] and the greater the degree of overweight as a child, the greater the likelihood that child will be overweight as an adult. 18,19 Extensive research addressing the intersection of TV use and child overweight has included known risk factors for child overweight, such as sociodemographics (e.g., gender, ethnicity, household income, parent education), 20,21 dietary intake (amounts and types of foods eaten), 13 presence of TV at meals, 12 perception of parental weight status 5,20 and measures of physical activity.…”
Section: Introductionmentioning
confidence: 99%